Hiding in Plain Sight: Discovering the Métis Nation in the Collection of Library and Archives Canada. LIBRARY AND ARCHIVES CANADA - Dombowsky, Philip (Archivaria, 2016)
Hiding in Plain Sight: Discovering the Métis Nation in the Collection of Library and Archives Canada. LIBRARY AND ARCHIVES CANADA. 11 February–22 April 2016. Curated by Beth Greenhorn, Al Benoit, William Benoit, and Carolyn Cook.